2007
DOI: 10.1128/aem.00593-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Quorum Sensing in Serratia marcescens AS-1 by Synthetic Analogs of N -Acylhomoserine Lactone

Abstract: Quorum sensing is a regulatory system for controlling gene expression in response to increasing cell density. N-Acylhomoserine lactone (AHL) is produced by gram-negative bacteria, which use it as a quorum-sensing signal molecule. Serratia marcescens is a gram-negative opportunistic pathogen which is responsible for an increasing number of serious nosocomial infections. S. marcescens AS-1 produces N-hexanoyl homoserine lactone (C 6 -HSL) and N-(3-oxohexanoyl) homoserine lactone and regulates prodigiosin product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 31 publications
6
128
0
1
Order By: Relevance
“…The A. hydrophila SSU WT strain, its various isogenic mutants and their corresponding complemented strains were grown directly in 3 ml LB medium contained in polystyrene tubes at 37 uC for 24 h with shaking. Biofilm formation was quantified according to a procedure described elsewhere (Morohoshi et al, 2007). Finally, biofilm formation results were normalized to 1610 9 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…The A. hydrophila SSU WT strain, its various isogenic mutants and their corresponding complemented strains were grown directly in 3 ml LB medium contained in polystyrene tubes at 37 uC for 24 h with shaking. Biofilm formation was quantified according to a procedure described elsewhere (Morohoshi et al, 2007). Finally, biofilm formation results were normalized to 1610 9 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
“…Such high-throughput screening has also led to the identification of two classes of molecules able to suppress V. cholerae virulence factor expression through modulation of either the noncanonical AHL receptor LuxN or the NtrC-like response regulator LuxO (189). Additionally, structure-based derivatiza-tion of previously identified antagonists has led to the discovery of multiple non-AHL pharmacophores with activity against LuxRtype proteins, including disubstituted imidazolium salts (183,190) and N-acyl cyclopentylamides (191,192).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…However, there are some data addressing these issues. Various compounds have been demonstrated to inhibit in vitro behaviors, including but not limited to P. aeruginosa biofilm formation (118,126,168,200,203), Serratia marcascens swarming and biofilm formation (192), and carbapenem production in Serratia spp. (186).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…Little is known about the antimicrobial effects of the fruit and no study has been found reporting its anti-quorum sensing activity. Therefore, this work aimed at evaluating the quorum sensing inhibitory potential of phenolic extracts obtained from E. brasiliensis fruit against commonly phenotypes regulated by quorum sensing in Chromobacterium violaceum, Aeromonas hydrophila and Serratia marcescens (Morohoshi et al, 2007;Pinto et al, 2007;Ponce-Rossi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%